Resilience among the elderly cared for by the Primary Healthcare Network in a city of Northeast Brazil - Ferreira, Camomila Lira; Santos, Lúcia Maria Oliveira; Maia, Eulália Maria Chaves (Revista da Escola de Enfermagem da USP, 2012)
The objective of this study is to evaluate the capacity of resilience, self-esteem and social support among the elderly by means of an exploratory study. The convenience sample consisted of elderly users of the public healthcare network in Natal-RN, Brazil, who answered the questionnaire and the Resilience, Self-Esteem and Social Support Scales. Participants were 65 seniors, with a mean age of 71 years, 81% female, with poor socio-economic conditions. It was found that the elderly participants have resilient characteristics, positive self-esteem and social support perceived as satisfactory, despite their losses and decline due to aging. Furthermore, moderate and positive correlations were observed between resilience and self-esteem, because as one increased, the other also increased. Therefore, it appears that resilience, considered a resource that assists development, favors staying well through this critical period, as well as the protective factors, which are important health indicators.